The Management Model of Waqf Land Empowerment in Improving Community Welfare in Lamsiteh Village, Aceh Besar District - Riyaldi, Muhammad Haris; Rahama, Cut Fadhila (Journal of International Conference Proceedings, 2024)
This study aims to elaborate the implementation of management model in empowering waqf land in the Lamsiteh village, and its impact on improving the community welfare. Lamsiteh village has land waqf managed by Baitul Mal Aceh (BMA) as nazhir. Therefore, it is vital to analyze the management, outcome and impact of the land waqf towards the comunity. This research was conducted qualitatively with interview and documentation procedures compiled through the data reduction, verification and drawing conclusions. The welfare of the village community was measured by using Maqashid Syariah indicators. Based on the results, it shows that the management of productive waqf of rice fields is carried out with a profit-sharing system (mukhabarah). The allocation of waqf results is still intended for consumptive dan religion purposes (hifzul ad-din), so it is not fully optimal in improving community welfare. In fact, there are many solutions offered, including intertwining partnerships with stakeholders to be able to finance management and empowerment waqf land, professional nazirs in managing productive waqf, and improving community welfare with comprehensive Maqashid Syari'ah are something that are still relevant to discuss.Keywords: Community welfare; Management model; Waqf land empowermentJEL Classification:  For papers in the economics field only.